Pengaruh Metode Maserasi Konvensional dan Berbantu Gelombang Mikro Terhadap Penapisan Fitokimia dan Standardisasi Ekstrak Peperomia pellucida L. - Priamsari, Margareta Retno; Kamila, Iffa; Sawal, Rizky Ardian Hartanto (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
Suruhan (Peperomia pellucida L.) is a medicinal plant with many benefits. The efficacy of medicinal plants is related to the results of phytochemical screening and standardization, which are reflected in the quality of the extracts produced. This study aims to assess the impact of extraction methods on the phytochemical screening profile and standardization of suruhan leaf extract. The samples were extracted using the maceration and microwave assisted extraction (MAE) method with 96% ethanol solvent. Next, phytochemical screening and standardization were carried out on both powder and extract. The data obtained was then analyzed descriptively. The results of phytochemical screening from both the maceration and MAE methods show that suruhan leaf extract contains flavonoids, saponins, phenols, tannins, steroids, triterpenoids and glycosides. The results of standardization of leaf extracts using the maceration method obtained water soluble essence content of 2.15%, ethanol dissolved essence content of 67.31%, drying loss of 9.68%, ash content of 37.2988%, specific gravity of 0.9805 g/mL, and Pb metal contamination 0.000 mg/L. Meanwhile, the results of standardization of the leaf extract ordered by the MAE method obtained a water soluble essence content of 30.06%, an ethanol dissolved essence content of 33.84%, a drying loss of 9.52%, an ash content of 38.1392%, a specific gravity of 0.8273 g/mL , and Pb metal contamination 0.061 mg/L.